Direct Color Observation of Light‐Driven Molecular Conformation‐Induced Stress. Issue 2 (16th December 2021) - Pujol‐Vila, Ferran; Escudero, Pedro; Güell‐Grau, Pau; Pascual‐Izarra, Carlos; Villa, Rosa; Alvarez, Mar
Abstract: Although usually complex to handle, nanomechanical sensors are exceptional, label‐free tools for monitoring molecular conformational changes, which makes them of paramount importance in understanding biomolecular interactions. Herein, a simple and inexpensive mechanical imaging approach based on low‐stiffness cantilevers with structural coloration (mechanochromic cantilevers (MMC)) is demonstrated, able to monitor and quantify molecular conformational changes with similar sensitivity to the classical optical beam detection method of cantilever‐based sensors (≈4.6 × 10 –3  N m –1 ). This high sensitivity is achieved by using a white light and an RGB camera working in the reflection configuration. The sensor performance is demonstrated by monitoring the UV‐light induced reversible conformational changes of azobenzene molecules coating. The trans‐cis isomerization of the azobenzene molecules induces a deflection of the cantilevers modifying their diffracted color, which returns to the initial state by cis‐trans relaxation. Interestingly, the mechanical imaging enables a simultaneous 2D mapping of the response thus enhancing the spatial resolution of the measurements. A tight correlation is found between the color output and the cantilever's deflection and curvature angle (sensitivities of 5 × 10 –3  Hue µm –1 and 1.5 × 10 –1  Hue (°) –1 ). These findings highlight the suitability of low‐stiffness MMC as an enabling technology for monitoring molecular changes with unprecedented simplicity, high‐throughput capability, and functionalities. Abstract : The combination of low‐stiffness mechanochromic cantilevers and real‐time color analysis enables a direct color observation and quantification of the light‐driven conformational changes of azobenzene molecules. A tight correlation is found between the cantilevers' color output and their deflection and curvature angle, with a similar surface stress sensitivity to the classical optical beam detection method of cantilever‐based sensors.